The Cabbage We Know as Jurisprudence: A Composition of One Layer upon Another - Thapa, Kamal Raj (Kathmandu School of Law Review, 2013)
This article is a narrative on the scope of jurisprudence, its scope and limitations that have to be analyzed in the light of the divisions and classifications that have penetrated the discipline. It relates the genesis of the confusions and complexities observable in jurisprudence, mostly pertaining to its definition and basic elements in which the former, seemingly, has no consensus. Various intellectuals and schools of thoughts have sought to explain the province of jurisprudence from their own confined approaches, including the popular positivists and naturalists whose idea of law is altogether divergent. Moreover, the historical, sociological, realist and economic schools have both solved and added to the complexities. However, the essence of the article is that jurisprudence, both in its scope and understanding, is extremely broad. Scholars and students in particular, need not confine their understanding to what is postulated earlier as to what jurisprudence means, rather are encouraged to comprehend the layers thoroughly and apply the fundamental tool of science, i.e. logic, and urged not to negate the significance of associating legal theory with social phenomena.